2010
DOI: 10.5012/bkcs.2010.31.9.2519
|View full text |Cite
|
Sign up to set email alerts
|

Control of Surface Chemistry and Electrochemical Performance of Carbon-coated Silicon Anode Using Silane-based Self-Assembly for Rechargeable Lithium Batteries

Abstract: Silane-based self-assembly was employed for the surface modification of carbon-coated Si electrodes and their surface chemistry and electrochemical performance in battery electrolyte depending on the molecular structure of silanes was studied. IR spectroscopic analyses revealed that siloxane formed from silane-based self-assembly possessed Si-O-Si network on the electrode surface and high surface coverage siloxane induced the formation of a stable solid-electrolyte interphase (SEI) layer that was mainly compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…For example, for Li 4 Ti 5 O 12 , carbon coating can significantly improve the C‐rate performance, cycle stability as shown Figure e, and stability with electrolyte . For big‐volume‐change electrode particles (e.g., silicon), carbon coating is also critical for stabilizing the ETN structures and SEI layer . However, it should be noted that for silicon, carbon‐coating is usually combined with a rational design of pore structure inside the particles to compensate the big volume change.…”
Section: Controlling Etn In Composite Electrodesmentioning
confidence: 99%
“…For example, for Li 4 Ti 5 O 12 , carbon coating can significantly improve the C‐rate performance, cycle stability as shown Figure e, and stability with electrolyte . For big‐volume‐change electrode particles (e.g., silicon), carbon coating is also critical for stabilizing the ETN structures and SEI layer . However, it should be noted that for silicon, carbon‐coating is usually combined with a rational design of pore structure inside the particles to compensate the big volume change.…”
Section: Controlling Etn In Composite Electrodesmentioning
confidence: 99%
“…2,3) It has been established that interfacial instability of Si electrode with electrolyte, i.e., the attack of LiPF 6 -derived acidic species (PF 5 , PF 3 O, HF) addi-tionally deteriorate the particle cracking event. [4][5][6] Our earlier work showed that for amorphous silicon suboxides, SiO x (x = 0.4, 0.85, 1.0 and 1.3), higher oxygen content induces to decrease initial electrolyte reduction but larger fraction of oxides is subjected to dissolution by acid (e.g., HF)-etching. 7) The control of anode-electrolyte interfacial reaction and the formation and composition of solid electrolyte interphase (SEI) has been suggested as an effective approach for enhancing the cycling performance of Si-based anodes for rechargeable lithium batteries.…”
Section: Introductionmentioning
confidence: 99%
“…7) The control of anode-electrolyte interfacial reaction and the formation and composition of solid electrolyte interphase (SEI) has been suggested as an effective approach for enhancing the cycling performance of Si-based anodes for rechargeable lithium batteries. [4][5][6][7][8][9][10] Lithium diffusivity is an intrinsic property of lithium ion-conducting electrode material. It is generally proposed that the rate of lithiation process of anode and cathode material is controlled by lithium diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10]18) Our earlier work showed that interfacial stabilization of pulsed laser deposited (PLD) Si film model electrode on Cu substrate by constructing the surface protective siloxane network at the electrode surface using dimethoxydimethylsilane (DMMS, (CH 3 ) 2 (CH 3 O) 2 Si) provides lithium diffusivity of 2.35×10 13 cm 2 /s which is approximately three orders lower than ~1.12×10…”
Section: )mentioning
confidence: 99%